Associations of MAP2K3 Gene Variants With Superior Memory in SuperAgers - Huentelman, Matthew J.; Piras, Ignazio S.; Siniard, Ashley L.; De Both, Matthew D.; Richholt, Ryan F.; Balak, Chris D.; Jamshidi, Pouya; Bigio, Eileen H.; Weintraub, Sandra; Loyer, Emmaleigh T.; Mesulam, M.-Marsel; Geula, Changiz; et al. (Frontiers in Aging Neuroscience, 2018)
Introduction: SuperAgers are adults age 80+ with episodic memory performance that is at least as good as that of average middle-aged adults. Understanding the biological determinants of SuperAging may have relevance to preventing age-related cognitive decline and dementia. This study aimed to identify associations between genetic variations and the SuperAging phenotype using Whole Exome Sequencing (WES). Methods: Sequence Kernel Association Combined (SKAT-C) test was conducted at the gene level including both rare and common variants in 56 SuperAgers and 22 cognitively-average controls from the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Results: The SuperAging phenotype was associated with variants in the Mitogen-Activated Protein Kinase Kinase 3 (MAP2K3) gene. Three single nucleotide polymorphisms (SNPs) contributed to the significance (rs2363221 [intron 1], rs2230435 [exon 5], rs736103 [intron 7]). Conclusions: MAP2K3 resides in a biological pathway linked to memory. It is in a signaling cascade associated with beta-amyloid mediated apoptosis and has enriched expression in microglia. This preliminary work suggests MAP2K3 may represent a novel therapeutic target for age-related memory decline and perhaps Alzheimer’s disease.